Human Resource Management Practices and Academics’ Performance - Wijaya, Muhammad Adhimawan; Hudiyah, Dewi; Marbun, Nova Laura Putri; Azzahra, Nurul Fitri (Universitas Muhammadiyah Prof. DR HAMKA., 2023)
The aim of this study was to investigate the effect of human resource management practices on the job satisfaction of academics in higher education institutions. Furthermore, there were 129 academics from several higher education institutions in West Java involved as participants in this study. The research instrument consisted of 30 items to assess human resource management practices and three items to assess job satisfaction. Additionally, SPSS 29.0 was used for data analysis. Based on the results of this study, there was a significant and positive association between job satisfaction and human resource management practices, including recruitment, selection, training and development, performance appraisal, rewards, recognition, and promotion prospects. The findings and statistical analysis of this study highlighted the effect of human resource management practices on the job satisfaction of academics in higher education institutions. In addition, it was expected that the novelty of this study would provide a significant contribution to human resource management practices and the current situation of job satisfaction in Indonesian higher education institutions, particularly in the public sector.